2018
DOI: 10.1016/j.jash.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Elevated preoperative blood pressures in adult surgical patients are highly predictive of elevated home blood pressures

Abstract: Blood pressure (BP) measurement during the presurgical assessment has been suggested as a way to improve longitudinal detection and treatment of hypertension. The relationship between BP measured during this assessment and home blood pressure (HBP), a better indicator of hypertension, is unknown. The purpose of the present study was to determine the positive predictive value of presurgical BP for predicting elevated HBP. We prospectively enrolled 200 patients at a presurgical evaluation clinic with clinic bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Of the forty-nine home blood pressure monitors provided, 46 (94%) were returned, consistent with our prior experience of adherence to such monitoring among study participants in the preoperative population (Schonberger et al 2018 ). The median number of blood pressure readings among these participants was 26 (IQR = 16-46).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Of the forty-nine home blood pressure monitors provided, 46 (94%) were returned, consistent with our prior experience of adherence to such monitoring among study participants in the preoperative population (Schonberger et al 2018 ). The median number of blood pressure readings among these participants was 26 (IQR = 16-46).…”
Section: Resultssupporting
confidence: 73%
“…Within the field of anesthesiology, the Merit-Based Incentive Program (MIPS) included hypertension screening in its 2007 anesthesiology specific quality metrics, and subsequent literature established plausible thresholds at which preoperative blood pressures appeared reasonably predictive of longitudinal blood pressure elevation (Schonberger et al 2012 ; Schonberger et al 2015 ; Schonberger et al 2018 ). Nevertheless, while isolated teams have attempted to bring hypertension screening and treatment into perioperative workflows (Pfister et al 2020 ), randomized interventional studies based on these efforts have remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Schonberger et al observed significantly higher preoperative office BP levels than home BP levels, and they confirmed that elevated preoperative BP values usually correspond to poorly controlled or even undiagnosed hypertension. 23 The incidence of poorly controlled or even undiagnosed hypertension in our patients, especially outpatients, might be relatively high because there are fewer opportunities for BP monitoring by a professional before surgery; this issue needs further study. Additionally, for outpatients, same-day surgery means taking a long trip to the hospital, having an irregular diet and sleeping at a hotel near the hospital before surgery, getting up early on the day of surgery and going through the tedious hospitalization procedures.…”
Section: Discussionmentioning
confidence: 92%
“…It is possible that such measurement does not represent a true “baseline” as it could be influenced by stress or premedication. However, it was demonstrated that BP measurements obtained on the day of the surgery were similar to those obtained via primary care [ 22 ]. Secondly, due to the fact that BP was measured in 5-min intervals, we chose not to quantify the duration of IOH in minutes but in episodes.…”
Section: Discussionmentioning
confidence: 99%